2019
DOI: 10.3389/fpsyg.2019.01864
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and Identity Processes in Two Domains: Mediational Roles of Worry, Rumination, Indecisiveness, Shame, and Guilt

Abstract: The objective of the study was to assess the relationships between two dimensions of perfectionism, that is, perfectionistic strivings and perfectionistic concerns, and identity processes in the domains of future plans and education. It was hypothesized that such consequences of perfectionism as worry, rumination, indecisiveness, and guilt and shame proneness would be mediators of the perfectionism–identity relationship. A total of 696 students took part in the study ( M age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 55 publications
(93 reference statements)
8
28
0
1
Order By: Relevance
“…observed that striving for perfection (similar to self-oriented perfectionism in the Hewitt and Flett's model) in late adolescence is associated with positive identity development and correlate with stronger identity commitment, higher identification with commitments undertaken, and higher exploration, while perfectionistic doubts, fear of criticism and negative evaluation of others (similar to socially-prescribed perfectionism) are associated with difficulties with commitment making. In the second study, Piotrowski (2019) confirmed the Luyckx's results and showed that such emotional and cognitive characteristics associated with perfectionism as indecisiveness, shame proneness, worry, and rumination are important mediators of the perfectionism-identity link. Other-oriented perfectionism has not been previously studied in the context of identity development.…”
Section: Attachment Perfectionism and Identitysupporting
confidence: 74%
See 3 more Smart Citations
“…observed that striving for perfection (similar to self-oriented perfectionism in the Hewitt and Flett's model) in late adolescence is associated with positive identity development and correlate with stronger identity commitment, higher identification with commitments undertaken, and higher exploration, while perfectionistic doubts, fear of criticism and negative evaluation of others (similar to socially-prescribed perfectionism) are associated with difficulties with commitment making. In the second study, Piotrowski (2019) confirmed the Luyckx's results and showed that such emotional and cognitive characteristics associated with perfectionism as indecisiveness, shame proneness, worry, and rumination are important mediators of the perfectionism-identity link. Other-oriented perfectionism has not been previously studied in the context of identity development.…”
Section: Attachment Perfectionism and Identitysupporting
confidence: 74%
“…In general, it must be stressed that the expected link between selforiented perfectionism and parental identity was smaller than anticipated. Based on the results of and Piotrowski (2019) we could expect stronger relationships. However, Luyckx and colleagues and Piotrowski studied the future plans identity domain (future plans clarity) and not the parental one.…”
Section: Perfectionism and Parental Identity Formationmentioning
confidence: 91%
See 2 more Smart Citations
“…Identity development, however, moves across various trajectories. Such characteristics as anxiety, indecision, depression which may hinder the process of making important decisions or increase doubts and difficulties at a later time, after making identity decisions, contributing to persistence of the identity crisis Piotrowski: How Good It Would Be to Turn Back Time 56 (Crocetti, Rubini, & Meeus, 2008;Crocetti, Klimstra, Keijsers, Hale, & Meeus, 2009;Luyckx et al, 2008;Piotrowski, 2019).…”
Section: Introductionmentioning
confidence: 99%